An Efficient Pairwise Key Establishment Scheme for Wireless Sensor Networks Using ORP (International Journal of Engineering and Computer Science, 2015)
Wireless sensor network has many application such as environment sensing, building safetymonitoring, earthquake prediction etc. Security is critical issue in sensor networks. A fundamental securityservice is to establish pairwise key shared between two sensor nodes, which is basis of other security such asencryption and authentication. The prime problem in key management is to establish secure keys between thesensor nodes. To avoid this pairwise key establishment is used. This scheme consists of two key pools. One keypool is hashed value of keys in another key pool. With the one-way hash function, this scheme can makeattackers get less key information from the compromised sensor nodes. Along with this Otway Rees protocol isused to provide integrity and authenticity. If direct path between two sensors are not present, then by using thisprotocol it is easy to find key with the help of intermediate node.